Transcriptome analysis reveals seven key immune pathways of Japanese flounder (Paralichthys olivaceus) involved in megalocytivirus infection. Issue 103 (August 2020) - Wu, Qian; Ning, Xianhui; Jiang, Shuai; Sun, Li
Abstract: Megalocytivirus is a serious viral pathogen to many farmed fish including Japanese flounder ( Paralichthys olivaceus ). In this study, in order to systematically identify host immune genes induced by megalocytivirus infection, we examined the transcription profiles of flounder infected by megalocytivirus for 2, 6, and 8 days. Compared with uninfected fish, virus-infected fish exhibited 1242 differentially expressed genes (DEGs), with 225, 275, and 877 DEGs occurring at 2, 6, and 8 days post infection, respectively. Of these DEGs, 728 were upregulated and 659 were downregulated. The majority of DEGs were time-specific and formed four distinct expression profiles well correlated with the time of infection. The DEGs were classified into diverse Gene Ontology (GO) functional terms and enriched in 27 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, approximately one third of which were related to immunity. Weighted co-expression network analysis (WGCNA) was used to identify 16 key immune DEGs belonging to seven immune pathways (RIG-I-like receptor signaling pathway, JAK-STAT signaling pathway, TLR signaling pathway, cytokine-cytokine receptor interaction, phagosome, apoptosis, and p53 signaling pathway). These pathways interacted extensively and formed complicated networks. This study provided a global picture of megalocytivirus-induced gene expression profiles of flounder at the transcriptome level and uncovered a set of key immune genes and pathways closely linked to megalocytivirus infection. These results provided a set of targets for future delineation of the key factors implicated in the anti-megalocytivirus immunity of flounder. Highlights: A total of 1242 differentially expressed genes were induced by megalocytivirus. The expressions of the DEGs were highly time-dependent and clustered into 4 groups. Sixteen key immune genes forming complex networks with each other were identified. The interactive key genes belonged to 7 immune pathways vital to antiviral immunity.